Murakami Haruki and Our Years of Pilgrimage - Hansen, Gitte Marianne; Tsang, Michael (Routledge, 2021)
This volume presents interdisciplinary perspectives on Haruki Murakami's work over four decades, covering topics such as history, space, translation, gender, literary influence, and interviews with translators and critics.